Millimeter‐Sized Hierarchical Porous Titanosilicate Supported Ultrafine Ag Nanoparticles as Highly Efficient Catalyst. Issue 45 (1st December 2022) - Wang, Minghui; Shu, Ting; Ge, Xinfeng; Hu, Jun; Liang, Yunxiao
Abstract: Developing easily recyclable noble metal nanoparticle‐based heterogeneous catalysts is highly desirable for the practical applications. Herein, a millimeter‐sized hierarchical porous titanosilicate (HPTS) was prepared by the multi‐template method. Various characterization results reveal that HPTS combines the structural advantages of monolith materials and nanomaterials. HPTS is used as an advanced support to construct the Ag/HPTS catalysts via the Ag + in situ reduction on its pore wall. Ag/HPTS shows high catalytic activity for 4‐nitrophenol (4‐NP) reduction with the TOF values of 3.91 min −1, which can be attributed to the ultrafine Ag NPs (2.04 nm) and the unique structure of HPTS. The 3D pass‐through macroporous channels facilitate mass transfer. The mesopores with ultra‐short channel remarkably enhance the accessibility of the active sites. The abundant mesopores and micropores effectively confine the Ag NPs size. Moreover, Ag/HPTS demonstrated good stability and recyclability. Abstract : The 3D continuous pass‐through macroporous channels allow fast mass transfer. Abundant mesopores with short channel remarkably enhance the accessibility of the active sites. The abundant micropores provide large amounts of anchoring sites for Ag NPs loading. The uniformly dispersed and ultrafine Ag NPs (2.04 nm) can transfer the interfacial electrons from BH4 − to 4‐NP − more efficiently.